Complete mitochondrial genome of a large-footed bat, Myotis macrodactylus (Vespertilionidae). (3rd September 2015) - Nam, Taek Woo; Kim, Hye Ri; Cho, Jae Youl; Park, Yung Chul
Abstract: The complete mitochondrial genome was sequenced and characterized newly from a large-footed bat, Myotis macrodactylus (Vespertilionidae). The total length of the M. macrodactylus genome is 17, 562 bp, with a base composition of 34.0% A, 29.9% T, 23.0% C and 13.0% G. A short sequence of CATACG is repeated 60 times in D-loop region. Amino acid of M. macrodactylus was 92.7% similar to that of M. formosus . Nucleotide similarity was 86.6% in all the other gene regions except for D-loop with low 66.8% similarity.